Brute ornament : Kamrooz Aram and Seher Shah - Alan Gilbert; Kamrooz Aram; Media Farzin; Murtaza Vali; Seher Shah; Shumon Basar (Dubai; Green Art Gallery, 2012)
With contributions by: Shumon Basar, Media Farzin, Alan Gilbert and Murtaza Vali
English
Keywords: Iran; N4390-5098 Visual Arts. Exhibitions